Heat input for preparing domestic hot water based on operational measurements in multi-unit buildings - Bartnicki, Grzegorz; Klimczak, Marcin (Instal, 2025)
The article presents the results of research of domestic hot water (DHW) installations in two complexes of multi-family residential buildings. The measurements focused on monitoring the DHW temperature and circulating water in selected points of the installations and in the DHW preparation system. Fluctuations in temperature in the DHW preparation system were demonstrated, which were greater in the case of the system with storage heaters. Despite the installation being equipped with thermostatic riser valves, changes in the temperature of circulating water returning from the installation occurred in the same way as changes in the temperature of DHW in its preparation system. It was also noted that the energy input for the preparation of DHW taken from the installation is much greater than the heat in the form of used hot water. Therefore, proper design of the domestic hot water and circulation installation of great importance but also its thermal protection (insulation, pipe routing, etc.) and proper hydraulic regulation.
Keywords: energy efficiency; circulation installation; renewable energy sources; energy consumption modeling